Mineral element content of oats (Avena sativa L.) in an acid sulphate soil area of Tupos village, northern Finland - Yli-Halla, Markku; Palko, Jukka (Agricultural and Food Science, 1987)
The mineral element content of oat grains grown in acid sulphate soils (n = 35) and other soils (n = 19) in Tupos was studied. In terms of P, K, Ca, Mg, S, Cu and Zn concentrations, Tupos oats did not differ from the averages and ranges presented for Finnish oats in other studies. Instead, Tupos oats were in general rich in Fe and Co and low in Se. High concentrations of Mn and Ni occurred in samples originating from acid sulphate soils. The lower the soil pH, the higher were the concentrations of Ni and Co in oats. Na and Ni were the only elements displaying a clear relationship between the concentration of the element in oats and the amounts of the element easily soluble in the soil. Tupos oats deviated less than Tupos timothy from the mineral contents of both these plant species usually reported in Finland. Limingan kunnan Tupoksen kylästä kerättiin 51 kpl kauran jyvänäytteitä, joista 35 kpl oli kasvanut happamaksi sulfaattimaaksi luokitelluilla pelloilla. Kun jyvien kivennäisainepitoisuudet määritettiin, todettiin, että ne sisälsivät fosforia, kaliumia, kalsiumia, magnesiumia, rikkiä, kuparia ja sinkkiä tavanomaiset määrät. Sen sijaan näytteiden rauta- ja kobolttipitoisuus oli suurehko ja seleenipitoisuus hyvin pieni. Muutamissa happamilla sulfaattimailta kerätyissä jyvänäytteissä oli tavallista enemmän mangaania ja nikkeliä. Mitä enemmän maassa oli helppoliukoista natriumia ja nikkeliä, sitä enemmän näitä alkuaineita oli kauran jyvissä. Jyvien koboltti- ja nikkelipitoisuudet olivat suurimmat happamimmilla kasvupaikoilla. Tupoksen alueen kauran jyvien kivennäisainepitoisuudet poikkesivat tavanomaisista arvoista vähemmän kuin samalla alueella kasvaneen timotein kivennäisainepitoisuudet.